The Effectiveness of Trichoderma Biofertilizer on the Vegetative Growth of Rice Plants - Dini Eka Putri; S Sutarman (Demeter: Journal of Farming and Agriculture, 2026)
This study aims to examine the effect of the combination of Trichoderma biofertilizer and liquid micro-nutrient fertilizer sprayed on the canopy at different time intervals and their interaction on the vegetative growth of rice plants. The treatments in this experiment were arranged factorially in a Randomized Block Design (RBD). The first factor was the combination of liquid micro-nutrient fertilizer and Trichoderma, consisting of without and with liquid fertilizer combination, while the second factor was the spraying interval, consisting of every week, every two weeks, and every three weeks. The experiment was repeated four times, resulting in 24 experimental units. The plant growth variables observed were plant height, number of tillers, and number of panicles. The interaction between the combination of liquid micro-nutrient fertilizer and Trichoderma and the spraying interval on the canopy significantly increased plant height but did not significantly affect the number of tillers and the maximum number of panicles. Spraying liquid biofertilizer and liquid microfertilizer every three weeks showed the highest results at a height of 55.27 cm. The combination of biofertilizer and microfertilizer has the potential to be applied to increase rice production.